Detection of alzheimer's disease using deep learning - Hasan, Mahmudul; Hassan, Syed Zafrul; Azmi, Tanzina Hassan; Hossain, Emtiaz (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.